Make way for her : and other stories - Cortese, Katie (University Press of Kentucky new poetry and prose series., 2018)
A girl afflicted with pyrokinesis tries to control her fire-starting long enough to go to a dance with a boy she likes. A woman trapped in a stalled marriage is excited by an alluring ex-con who enrolls in her YMCA cooking class. A teen accompanies her mother, a prestigious poet, to a writing conference where she navigates a misguided attraction to a married writer -- who is, in turn, attracted to her mother -- leaving her "inventing punishments for writers who believe in clichés as tired as broken hearts."In this affecting collection, Katie Cortese explores the many faces of love and desire. Featuring female narrators that range in age from five to forty, the narratives in Make Way for Her speak to the many challenges and often bittersweet rewards of offering, receiving, and returning love as imperfect human beings. The stories are united by the theme of desperate love, whether it's a daughter's love for a parent, a sister's for a sibling, or a romantic love that is sometimes returned and sometimes unrequited. Cortese's complex and multilayered stories play with the reader's own desires and anticipations as her characters stubbornly resist the expected. The intrepid girls and women in this book are, above all, explorers. They drive classic cars from Maine to Phoenix, board airplanes for the first time, and hike dense forests in search of adventure; but what they often find is that the most treacherous landscapes lie within. As a result, Make Way for Her explores a world of women who crave knowledge and experience, not simply sex or love